Protecting your library's digital sources : - Kahn, Mirim B. (American Library Association, 2004)
Preventing common causes of loss -- Planning for the worst : loss of computer operations -- Basic considerations in disaster response planning -- Disaster response planning -- Disaster response : when everything goes wrong -- Disaster response planning for hardware and physical storage media -- Protecting data for long-term retention -- Decision-making for today and tomorrow -- The future : organizations involved with the study of the preservation of electronic records -- Checklists.